Aplikasi Penyandian Pesan Teks dengan menggunakan Metode Block Chiper Mode ECB - Manurung, Francius (MEANS (Media Informasi Analisa dan Sistem), 2018)
Encoding of text messages is very necessary to encode a message so that it is not stolen by irresponsible parties. Cryptography is one technique that can be used to carry out security messages, namely by encoding original messages that are understood to be incomprehensible data. Cryptographic techniques are used using the Block Cipher mode ECB method that works by using 64-bit keys and an iterative method consisting of linear steps (such as XOR and key applications). ECB block cipher mode application is to use J2ME as a testing tool. The text message will be entered into Netbeans and tested for the results of encryption and decryption. The design of system testing is done in several stages, namely making use case diagrams, Activity diagrams, Sequency diagrams and design interfaces